President's Podium: Communication: Not a One-Way Speech but a Two-Way Conversation - Optometrists, Canadian Association of (Canadian Journal of Optometry, 2026)
The opportunity to reach 2,700 optometrists through the simple act of setting pen to paper is a sobering thought to a new President. And yet, even as I write this message, it is with the intention of using a further technological intermediary - the Facsimile, or FAX, machine to get it to the CAO office where, presumably, it will be further processed through the CJO•RCO's typesetting and publishing operations before being communicated to you, the members of the Canadian Association of Optometrists.